Caracterización fenotípica de 7 líneas avanzadas de fréjol (Phaseolus vulgaris L.) obtenidas por selección individual en la zona de Quevedo. - Pincay Loor, Ronald (2015)
This research was conducted in the town of Quevedo at the experimental farm "La María" from the UTEQ located at Km 7 Via Quevedo - El Empalme, whose geographical coordinates are:. 79 ° 47 'West longitude . and 01 ° 32 'south latitude, 76 meters, the overall objective of this study was: To determine the phenotypic characteristics of 7 advanced lines of beans, adaptability and bean crop management, and specific objectives were: Establish lines of beans, that are best suited to the climatic conditions of the area of study and identify the potential performance of the materials studied. The lines studied were 7: SER 03, 08 and 31; EVG 02, 06, 16 and CAL 96, which corresponded to the treatments of study in the area of Quevedo. Experimental design Randomized Complete Block with 7 treatments and 4 replications was used. Tuckey test at 95% probability was used to establish the statistical differences between the averages of the lines. …